Contaminación lumínica en el Barrio de Belgrano, Buenos Aires, Argentina - Lazzeroni, Claudia Florencia; Guerrero, Elsa Marcela; Garcia, Beatriz Elena (Universidad Central de Venezuela, 2020)
Fil: Lazzeroni, Claudia Florencia. Universidad Nacional del Centro de la Provincia de Buenos Aires; Argentina